2021
DOI: 10.3233/shti210408
|View full text |Cite
|
Sign up to set email alerts
|

Practical Challenges of Creating and Managing the “Barrier-Free Basic Plan” for Better Accessibility in Cities by Local Governments in Japan

Abstract: The Barrier-Free Basic Plan (BFBP) of Japan is based on Article 25 in the Act on the Promotion of Smooth Transportation, etc. of Elderly Persons, Disabled Persons, etc., abbreviated as the “Barrier-Free Act”. BFBPs are created by municipal governments and play a crucial role in progressing the accessibility of existing buildings/facilities in cities. However, the number of municipal governments which have their own BFBPs stands at only 304 out of a total of approximately 1700 municipalities in 2020. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(3 reference statements)
0
0
0
Order By: Relevance
“…Many studies have shown that involving knowledge users in the knowledge creation process significantly and positively impacts the implementation of innovation ( 5 , 6 ). It also positively influences individual changes in knowledge, attitudes, and beliefs ( 7 9 ). The benefits of engaging stakeholders in the implementation process have been supported in the knowledge production process ( 4 , 7 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that involving knowledge users in the knowledge creation process significantly and positively impacts the implementation of innovation ( 5 , 6 ). It also positively influences individual changes in knowledge, attitudes, and beliefs ( 7 9 ). The benefits of engaging stakeholders in the implementation process have been supported in the knowledge production process ( 4 , 7 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to contextual factors (e.g., recent emphasis on universal accessibility issues, large number of universal accessibility measures and administrative rules) ( 17 ) and complexities lying within municipal organizations (e.g., multiple hierarchy levels, staff retention, large number of employees and administrative units, diversity of actors and stakeholders) ( 9 , 17 – 19 ). By 2050, it is estimated that more than two-thirds of the world's population will live in urban areas ( 20 ).…”
Section: Introductionmentioning
confidence: 99%